Pendampingan Literasi Bahasa Berbasis Sosiolinguistik untuk Meningkatkan Komunikasi Siswa di Sekolah - Indramini Indramini; Ilmiawan Ilmiawan (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
This study aims to describe the implementation of sociolinguistics-based language literacy mentoring activities in improving students' communication skills at SMA Muhammadiyah 1 Unismuh Makassar. The program was conducted in response to communication challenges among students, particularly in the use of polite language, communication confidence, and the ability to adapt language according to social contexts in the school environment. The approach used in this study was descriptive qualitative. The subjects were students who participated in the language literacy mentoring activities. Data collection techniques were carried out through observation, interviews, documentation, and assessment of student communication practices. The results of the study indicate that sociolinguistics-based language literacy mentoring activities made a positive contribution to improving students' communication skills. Students experienced improvements in the use of polite language, speaking courage, ability to express opinions, and participation in group discussions. In addition, students were also better able to adjust their language use according to formal and informal situations in the school environment. The application of methods such as group discussions, communication simulations, role plays, and language games proved effective in creating interactive and contextual learning. The findings also show that the sociolinguistic approach helped students understand the social functions of language and strengthened their awareness of appropriate communication practices in different interaction settings. These activities also contributed to the formation of students' social character through the habit of polite and effective communication. Overall, sociolinguistics-based language literacy mentoring was able to improve communication skills while shaping students' language ethics in everyday life. Furthermore, the program contributed to fostering positive communication culture, social interaction skills, and character development among students. Therefore, this approach is recommended as a sustainable learning strategy to improve the quality of student communication in schools and can serve as an alternative model for strengthening literacy, communication competence, and character education in educational institutions.